(untitled) (Texas Journal of Philology, Culture and History, 2024)
Comparative phraseology is a branch of linguistics that studies parallels and similarities in phraseological turns of phrase of different languages. This study considers the principles and methods of analysis of comparative phraseology to identify common and different features in the set expressions of different languages